2016
DOI: 10.1016/j.polymdegradstab.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the non Fickian water absorption in polyamide 6

Abstract: This paper investigates the water absorption of polyamide 6. The high amount of absorbed water in the polymer and the large resulting decrease in the glass transition temperature (Tg) leads to a non Fickian water diffusion when samples are immersed, which is a significant difficulty when trying to model the water profile in thick specimens. The aim of this study is to be able to model this particular behaviour based on physical considerations. First, it is shown that the non Fickian water diffusion is caused b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 25 publications
5
55
0
Order By: Relevance
“…Water uptake in the Nylon 6 appears to follow Henry's law for low water activity (below a=0.5), for higher activity water quantities deviate from this law. Similar results were observed in previous studies of bulk polyamide [6], [17]. These studies showed that the deviation is due to cluster creation inside the material, and it appears to be controlled by the Eq.…”
Section: Water Sorptionsupporting
confidence: 90%
See 4 more Smart Citations
“…Water uptake in the Nylon 6 appears to follow Henry's law for low water activity (below a=0.5), for higher activity water quantities deviate from this law. Similar results were observed in previous studies of bulk polyamide [6], [17]. These studies showed that the deviation is due to cluster creation inside the material, and it appears to be controlled by the Eq.…”
Section: Water Sorptionsupporting
confidence: 90%
“…Then, we subtract the linear term from the initial maximal moisture content and identify b and m over the second part of the curve. These parameters appear to be independent of the temperature as previously shown in [6], [17]. In the case of Nylon 6 fibres we obtain the following parameters: H 0 = 1.39; E a = -7kJ.mol -1 ; b = 3; m = 7.…”
Section: Eqsupporting
confidence: 80%
See 3 more Smart Citations